1970
DOI: 10.1039/c29700001066
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of a new alkaloid, stemofoline, from Stemona japonica

Abstract: The structure (I) of a new alkaloid, stemofoline isolated from the stems and leaves of Stemona japonica has been determined by X-ray crystallographic analysis of its hydrobromide monohydrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
74
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 0 publications
1
74
0
Order By: Relevance
“…The parent compound of this class, (4Z)-stemofoline (1; Scheme 1) was isolated and characterized 1970 by Irie et al [4] and reported again in 2001 together with (11E)-and (11Z)-1',2'-didehydrostemofoline (2) from S. collinsae [5]. A compound of identical chemical constitution was described from Asparagus racemosus [6] [7] as asparagamine A ± whose relationship to 1',2'-didehydrostemofoline (2) is a major topic of this contribution.…”
mentioning
confidence: 99%
“…The parent compound of this class, (4Z)-stemofoline (1; Scheme 1) was isolated and characterized 1970 by Irie et al [4] and reported again in 2001 together with (11E)-and (11Z)-1',2'-didehydrostemofoline (2) from S. collinsae [5]. A compound of identical chemical constitution was described from Asparagus racemosus [6] [7] as asparagamine A ± whose relationship to 1',2'-didehydrostemofoline (2) is a major topic of this contribution.…”
mentioning
confidence: 99%
“…The absolute configuration of 2 is not known but is assumed based on the known configurations of Stemona alkaloids with similar C,D-ring structures. 6,[9][10][11][12][13][14][15][16][17] The X-ray structure of 2 also showed that the piperidine A-ring adopts a chair-like conformation and is connected to the B-and C-rings through an ether bridge between C-1 and the quaternary acetal carbon C-9 readily identified in the 13 C NMR spectrum.…”
mentioning
confidence: 99%
“…2 A few of these alkaloids do not fit these five structural groups and have a more complex bridged structure or ring structures that most likely arises from initial oxidative cleavage of the pyrrolo [1,2-a] presence of the C-and D-ring system that is typically found in the stemoamide group of alkaloids, including stemofoline (1). 1,6,[9][10][11][12][13][14][15][16][17] The 13 C/DEPT NMR spectra of 2 indicated four methine carbons, and six methylene carbons and, unlike the other Stemona alkaloids, except 1 and its didehydro and 2'-hydroxy derivatives, 2 a quaternary carbon at  120.4 was apparent, indicative of a acetal-like structure (C-9).…”
mentioning
confidence: 99%
“…5 ) Irie et al recently isolated a new alkaloid named stemofoline (II) from leavcs and stems of this plant and established the structure as II by X-ray crystallographic analysis. 6 ) However, the insecticidal activity of the individual alkaloid has never been examined up to now.…”
mentioning
confidence: 99%